MYB proteins: Versatile regulators of plant development, stress responses, and secondary metabolite biosynthetic pathways - Bhatt, Preshita A.; Gurav, Tanuja P.; Kondhare, Kirtikumar R.; Giri, Ashok P. (International Journal of Biological Macromolecules, 2025)
MYB proteins are ubiquitous in nature, regulating key aspects of plant growth and development. Although MYB proteins are known for regulating genes involved in secondary metabolite biosynthesis, particularly phenylpropanoids, their roles in terpenoid, glucosinolate, and alkaloid biosynthesis remain less understood. This review explores the structural and functional differences between activator and repressor MYB proteins along with their roles in plant growth, development, stress responses, and secondary metabolite production. MYB proteins serve as central hubs in protein-protein interaction networks that regulate expression of numerous genes involved in the adaptation of plants to varying environmental conditions. Thus, we also highlight key interacting partners of MYB proteins and their roles in these adaptation mechanisms. We further discuss the mechanisms regulating MYB proteins, including autoregulation, epigenetics, and post-transcriptional and post-translational modifications. Overall, we propose MYB proteins as versatile regulators for improving plant traits, stress responses, and secondary metabolite production.
Keywords: Activator; defense; Development; MYB protein; Repressor; Secondary metabolites